The Influence of Corporate Social Responsibility Practices and Environmental Social Governance Performance on Company Asymmetric Information (Empirical Study on Industrial Companies Listed on the Indonesia, Malaysia, and Singapore Stock Exchanges in 2018-2022) - Evy Steelyana Wiyarti; Julia Jessica (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
The purpose of this study is to obtain empirical evidence of CSR practices (CSR_rep, CSR_com, CSR_ass, and GRI) and ESG performance (ENVscr, SOCscr, and GOVscr) of companies on the level of asymmetric information (bid-ask spread) contained in companies in Indonesia, Malaysia, and Singapore. The research method was conducted using a quantitative approach and panel data regression on 40 companies listed on the Indonesia Stock Exchange, 10 companies listed on the Malaysia Stock Exchange, and 10 companies listed on the Singapore Stock Exchange. The analysis technique was carried out by multiple linear regression analysis using the SPSS20 tool. The results showed that all independent variables, namely CSR practices consisting of CSR_rep, CSR_com, CSR_ass, and GRI and ESG performance consisting of ENVscr, SOCscr, and GOVscr, showed a negative and significant relationship with bid-ask spread. Thus, it can be concluded that the practice of Corporate Social Responsibility and the Environment Social Governance performance has a negative and significant effect on the on corporate asymmetric information as a dependent variable.